Banking for Family Business A New Challenge for Wealth Management - Caselli, Stefano; Gatti, Stefano (Springer Berlin Heidelberg : Imprint: Springer, 2005)
1 2 Laurent Huck and Sergio Trezzi During the last 5 years the asset management industry has been constantly invested by events which have required top management of major com- nies to rethink their business model, while preserving their company's mission. From the Internet bubble easy growth model to a strong cost control - vironment in 2000-2003, many financial institutions have undertaken structural changes in order to reap the opportunities offered by the "new" market. Hints of globalization have actually been around for several decades, even though they made only a modest impact; however, the availability of global capital and advances in communication technology have emp- sized the process of internationalization and the tools available to connect and integrate business activities to answer to more complex needs of c- ents. Moreover, the financial scandals and the review of mutual fund trade activity in the US by the Attorney General Elliot Spitzer have highlighted the importance to focus all efforts on renewing the confidence of prof- sional investors and their clients who have entrusted their capital to asset managers. Therefore, there is a growing need in the market to reinforce the concept of "Shared Positive Values" among the entire industry and among its stakeholders.